The Relationship Between Zakat, Infaq, Sadaqah, Economic Factors With Poverty In Indonesia - Pebruary, Silviana Pebruary; Isna Amara (IAIN Langsa, 2024)
This research intends to examine the relationship of Zakat, Infaq, and Sadaqah (ZIS), economic growth, education, minimum wage, and unemployment to poverty in Indonesia. The data used is secondary data, which is obtained through access to reports from the Central Bureau of Statistics and the National Amil Zakat Agency. The analysis was conducted using Eviews with panel data regression method, combining time series data from 2019 to 2023 and cross-section data from 34 provinces in Indonesia. The results showed that Zakat, Infaq, and Sadaqah (ZIS), economic growth, education, and minimum wage have no effect on poverty, because the probability value is greater than 5%, meanwhile, unemployment is proven to have an influence on poverty with a probability value of 0.0002 and a coefficient of 42.64756. This means that every 1% increase in the unemployment rate can increase the poverty rate by 42.64756. It is expected that the results of this study can be a reference for policymakers, practitioners, and other researchers in formulating strategies and programs to reduce poverty in Indonesia.